2016
DOI: 10.5897/ajb2016.15690
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of yield and nutritional value of soybean sprouts by persimmon fruit powder

Abstract: Large amount of soybean sprouts has been produced for human consumption in Korea for a long time. Various techniques and production methods have been implied to enhance the quality and yield of soybean sprouts. The objective of the present study was to investigate the effect of persimmon fruit powder treatment on yield and nutritional value of soybean sprouts. The sprout yield was increased by 16% with the addition of 5% (w/v) persimmon fruit powder during seed soaking. Vitamin C and polyphenol content were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…K-0.05% seemed to be the most appropriate concentration to obtain healthier sprouts. Our results were in part consistent with Kim et al [43], who demonstrated that seeds soaked with increasing concentrations of persimmon fruit powder produced sprouts proportionally richer in amino acids, ascorbic acid, and polyphenols. The amino acid-based biostimulants promoted polyphenol production [44] by stimulating nitrogen metabolism enzymes involved in the synthesis of these compounds [45].…”
Section: Effects Of Biostimulant Seed Pre-treatment and Light Quality On Sprout Bioactive Compoundssupporting
confidence: 93%
See 1 more Smart Citation
“…K-0.05% seemed to be the most appropriate concentration to obtain healthier sprouts. Our results were in part consistent with Kim et al [43], who demonstrated that seeds soaked with increasing concentrations of persimmon fruit powder produced sprouts proportionally richer in amino acids, ascorbic acid, and polyphenols. The amino acid-based biostimulants promoted polyphenol production [44] by stimulating nitrogen metabolism enzymes involved in the synthesis of these compounds [45].…”
Section: Effects Of Biostimulant Seed Pre-treatment and Light Quality On Sprout Bioactive Compoundssupporting
confidence: 93%
“…Consistent with this hypothesis, previous studies demonstrated that blue light promoted the expression of genes involved in the modulation of the ascorbic acid [48][49][50]. LQ regimes also alter the metabolism of phenolic compounds, which are generally more abundant in light-than in dark-grown sprouts [43,46,49]. The higher percentages of red and blue light may have stimulated soybean polyphenol synthesis as observed in several crop species [48], enhancing the expression of several related genes [51].…”
Section: Effects Of Biostimulant Seed Pre-treatment and Light Quality On Sprout Bioactive Compoundssupporting
confidence: 52%
“…After 30 min, the absorbance was detected at 517 nm using a SPECTROstar Nano. The data were calculated as a scavenging effect using the equation reported in a previous study [38]. We used a plotted curve to calculate the 50% inhibitory concentration of 0.2 mM DPPH (IC 50 ) and expressed the results in µL/mL.…”
Section: Determination Of Dpph Free Radical Scavengingmentioning
confidence: 99%
“…Modification of sprouts' nutritional quality may also be achieved with the application of many chemicals (isolated or in mixtures) (Table 5). Examples include oregano extract, fish protein hydrolysate, peptides (e.g., lactoferrin) (Randhir et al, 2004a, b), marine protein hydrolysates (Ramakrishna et al, 2019), Saccharomyces cerevisiae and Salix daphnoides bark extracts (Gawlik-Dziki et al, 2013), tea tree extract (Viacava and Roura, 2015), H 2 O 2 (Świeca, 2015), persimmon fruit powder (Kim et al, 2016), amino acids (e.g., phenylalanine, methionine, tryptophan, tyrosine) (Pérez-Balibrea et al, 2011;Seo et al, 2015;, CaCl 2 and sucrose (Sim et al, 2019), glucose (Wei et al, 2011), and other saccharides (e.g., chitosan) (Lee et al, 2005;Qiang et al, 2005) or plant growth regulators (Abellán et al, 2019;Moreira-Rodríguez et al, 2017;Pérez-Balibrea et al, 2011). Enrichment of the growing medium takes place at the stage of pre-sowing treatment, and also during the further stages of sprouting.…”
Section: Influence Of Chemical Substances and Natural Mixtures Application On Sprouts Modificationmentioning
confidence: 99%